Prospective associations between sleep disturbances and cannabis use among Veterans: A behavioral economic approach. (November 2022) - Berey, Benjamin L.; Aston, Elizabeth R.; Kearns, Nathan T.; McGeary, John E.; Borsari, Brian; Metrik, Jane
Highlights: Veterans reported on sleep disturbances, cannabis demand, and cannabis use indices. Sleep disturbances were prospectively linked to cannabis use frequency and quantity. Intensity and O max mediated relations between sleep disturbances and cannabis use frequency, quantity, and problems. Sleep disturbances remained indirectly associated with cannabis use quantity and problems via O max even after controlling for baseline levels of each 12-month cannabis use outcome. Abstract: Background: Veterans often use cannabis for sleep despite limited evidence of its efficacy. Moreover, how sleep disturbances impact cannabis use longitudinally is unclear. We applied a behavioral economic framework to examine whether sleep disturbances and cannabis demand (i.e., relative value) were related risk-factors for future cannabis use and problems. Methods: Veterans deployed post-9/11/2001 who reported past 6-month cannabis use at baseline ( n  = 126) completed surveys on their sleep disturbances, demand via the Marijuana Purchase Task (MPT), and cannabis use. Mediation analyses using Hayes' PROCESS Macro and zero-inflated negative binomial models tested indirect effects of baseline sleep disturbances on 12-month cannabis use frequency, quantity, and problems via 6-month cannabis demand (i.e., intensity, O max, P max, and breakpoint). Results: Only O max (i.e., maximum expenditure for cannabis) was a significant mediator for 12-month cannabis use quantity and problems when examined concurrently with other demand indices after controlling for covariates. Intensity (i.e., purchase at zero cost) was a significant mediator for 12-month cannabis use frequency when examined concurrently with other demand indices in models controlling for lifetime cannabis use, but not past 30-day use at baseline. Conclusion: Cannabis demand, specifically intensity and O max, may help to identify Veterans with sleep disturbances who are at increased risk for escalating their cannabis use. Subsequent research should assess the extent that sleep disturbances impact cannabis demand in the context of withdrawal, which will inform novel prevention and intervention strategies geared toward reducing negative cannabis-related outcomes among Veterans.